TAX AVOIDANCE DECISIONS WITH THIN CAPITALIZATION AND CAPITAL INTENSITY MODERATED BY SALES GROWTH - Nur Kholisah, Yuni Isna; Pratiwi, Adhitya Putri (Universitas Jember, 2024)
ABSTRACTThis research aims to provide information about the effects of thin capitalization and capital intensity on decisions taken by management to avoid paying taxes by adding sales growth as a moderating effect. The sample used is the properties and real estate sector listed on the Indonesia Stock Exchange during 2107-2021, namely 15 companies with a total research population of 81 companies, where the sample was determined using a purposive sampling method. Panel data regression analysis and moderation regression were used to regress research using the statistical tool e-views 10 with the results that thin capitalization influences tax avoidance, while capital intensity has no effect on tax avoidance. The interaction results of sales growth variables do not moderate the effect of thin capitalization and capital intensity on tax evasion.Keywords: Capital intensity; Sales Growth; Tax Avoidance; Thin Capitalization ABSTRAKRiset ini bertujuan untuk memberikan bukti empiris mengenai efek dari thin capitalization dan capital intensity terhadap keputusan yang diambil oleh manajemen untuk menghindari kewajiban pembayaran pajak dengan menambahkan variabel pertumbuhan penjualan sebagai efek moderasi. Sampel yang digunakan adalah sektor properti dan real estate yang listing pada Bursa Efek Indonesia selama 2017-2021 yakni sebanyak 15 perusahaan dengan total populasi penelitian adalah 81 perusahaan, di mana sampel ditentukan menggunakan metode purposive sampling. Analisis regresi data panel dan regresi moderasi digunakan untuk meregresi penelitian dengan alat bantu statistik e-views 10 dengan hasil thin capitalization memiliki pengaruh pada penghindaran pajak, sedangkan capital intensity tidak memiliki pengaruh pada penghindaran pajak. Hasil interaksi variabel pertumbuhan penjualan tidak memoderasi pengaruh thin capitalization dan capital intensity pada penghindaran pajak.Kata Kunci: Capital Intensity; Penghindaran Pajak; Pertumbuhan Penjualan; Thin Capitalization